2011
DOI: 10.1002/eji.201141555
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic cell death of human ovarian cancer cells induced by cytosolic poly(I:C) leads to myeloid cell maturation and activates NK cells

Abstract: Owing to high rates of tumor relapse, ovarian cancer remains a fatal disease for which new therapeutic approaches are urgently needed. Accumulating evidence indicates that immune stimulation may delay or even prevent disease recurrence in ovarian cancer. In order to elicit proinflammatory signals that induce or amplify antitumor immune reactivity, we mimicked viral infection in ascites-derived ovarian cancer cells. By transfection or electroporation we targeted the synthetic double-stranded RNA poly(I:C) intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…RLH ligands have been shown to induce the release of type I IFN in cancer cells mediated by IRF-3/7 and NF-kB signaling. 19,[21][22][23] To confirm intact RLH signaling in pancreatic cancer cells, we transfected Panc02 cells with ppp-RNA or poly(I:C), which induced IFN-b mRNA expression as well as CXCL10 and IL-6 secretion in a dose-dependent manner ( Figure 1a and Supplementary Figures 1a and b). In addition, treatment of Panc02 tumor cells with RLH ligands resulted in cell death (Figure 1b and Supplementary Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RLH ligands have been shown to induce the release of type I IFN in cancer cells mediated by IRF-3/7 and NF-kB signaling. 19,[21][22][23] To confirm intact RLH signaling in pancreatic cancer cells, we transfected Panc02 cells with ppp-RNA or poly(I:C), which induced IFN-b mRNA expression as well as CXCL10 and IL-6 secretion in a dose-dependent manner ( Figure 1a and Supplementary Figures 1a and b). In addition, treatment of Panc02 tumor cells with RLH ligands resulted in cell death (Figure 1b and Supplementary Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Others reported that treatment of human ovarian cancer cells with RLH ligands resulted in phagocytosis of apoptotic tumor cells by monocyte-derived DCs and DC activation. 22,23 Together, these findings indicate that RLH-induced tumor cell death may promote adaptive immunity against tumors. However, mechanisms leading to DC activation and the impact on tumor antigen cross-presentation by DCs, which defines immunogenic cell death, have not been explored.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…We first determined potency of these short ssRNA in eliciting antiviral responses in a human ovarian epithelial carcinoma cell line (SKOV3 cells), which have been previously used as a model to study the immunogenicity of different types of RNA [38][39][40]. Using IFNb expression as a benchmark for antiviral responses, our data showed that only 3p-ssRNA with longer than 60 nt induced IFNb, whereas the removal of the 3p group completely abolished this effect, as demonstrated in the case of 3p-80nt-ssRNA (Fig.…”
Section: Wang Et Almentioning
confidence: 99%
“…[51][52][53][54][55] One of the side effects of poly (I:C) is induction of toxic cytokines, so its use in cancer is limited. [56][57][58] In our study, by encapsulating zoledronic acid and poly (I:C) in LCP, the effective doses of both poly (I:C) and zoledronic acid could be decreased, so this formulation may have less toxic effects.…”
Section: Codelivery Of Poly (I:c) and Zoledronic Acid Had Superior Cymentioning
confidence: 99%